PEMANFAATAN MIKROALGA Chlorella sp DALAM MENURUNKAN BAKU MUTU POLUTAN LIMBAH CAIR INDUSTRI SAGU - Hartini, Fitri; Restuhadi, Fajar; Dahril, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
AbstractThis research aimed to get the potential concentration of sago wastewater optimum with microalgae Chlorella sp to reduce pollutant wastewater sago. Research was carried out by emplemented a Randomized Completely Design (RCD) with five treatments, namely: P0 (1000 ml sago wastewater without addition of microalgae), P1 (250 ml microalgae: 1000 ml sago wastewater), P2 (250 ml microalgae: 800 ml sago wastewater), P3 (250 ml microalgae: 600 ml sago wastewater), P4 (250 ml microalgae : 400 ml sago wastewater). Results showed that the concentration of sago wastewater and treated with microalgae Chlorella sp significantly reduced the COD, BOD, and TSS. The best treatment is P4 with COD 277,33 mg/L; BOD 125,33 mg/L; pH 7,04; and TSS 83,66 mg/L. Keywords : Chlorella sp, sago indusrial wastewater, COD, BOD, TSS, pH